2020
DOI: 10.31557/apjcp.2020.21.11.3279
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Some Non-Invasive Biomarkers in the Early Diagnosis and Staging of Egyptian Breast Cancer Patients

Abstract: Stage at which diagnosis occurs is an important predictor of breast cancer survival and quality of life, so there is an urgent need for early diagnostic indicators (Gao et al., 2013). CEACAM1, is a transmembrane glycoprotein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…These biomarkers' cutoff values, sensitivities, and specificities were effective in early separating BC from controls. Furthermore, serum visfatin levels are higher as tumor size and BC stage increased [15]. An earlier study revealed that the mean serum visfatin level was vastly higher in BC patients than in controls, indicating that it may be used as a biomarker for postmenopausal women [37].…”
Section: Resultsmentioning
confidence: 99%
“…These biomarkers' cutoff values, sensitivities, and specificities were effective in early separating BC from controls. Furthermore, serum visfatin levels are higher as tumor size and BC stage increased [15]. An earlier study revealed that the mean serum visfatin level was vastly higher in BC patients than in controls, indicating that it may be used as a biomarker for postmenopausal women [37].…”
Section: Resultsmentioning
confidence: 99%
“…As summarized in Table 3 and as reviewed by Dalamaga et al. ( 213 ), elevated levels of eNAMPT are present in cancer patients, positively correlating with tumor size and cancer stage ( 23 , 214 , 219 , 227 , 232 , 239 , 241 246 ). eNAMPT levels in cancer patients could also be (negatively) correlated with disease-free and overall survival and (positively) with lymph node invasion and/or metastasis ( 214 , 232 , 245 , 247 ).…”
Section: Enampt In Diseasementioning
confidence: 87%
“…Numerous studies of samples obtained from cancer patients assessed the association between circulating eNAMPT levels on the one hand, and cancer size/stage, patient survival or specific biomarkers, on the other. As summarized in Table 3 and as reviewed by Dalamaga et al (213), elevated levels of eNAMPT are present in cancer patients, positively correlating with tumor size and cancer stage (23,214,219,227,232,239,(241)(242)(243)(244)(245)(246). eNAMPT levels in cancer patients could also be (negatively) correlated with disease-free and overall survival and (positively) with lymph node invasion and/or metastasis (214,232,245,247).…”
Section: Clinical Studiesmentioning
confidence: 89%
“…It was discovered that it plays a role in breast cancer because a study found that the serum level of visvatin was significantly higher in patients with various stages of breast cancer than in benign and control groups. Additionally, the concentration of visvatin gradually rose in proportion to the tumor's growth (12) . When postmenopausal status is further examined, it is discovered that postmenopausal breast cancer patients have consistently higher serum visvatin levels than the control group (13,14) , whereas premenopausal breast cancer patients have higher serum visvatin levels.…”
Section: Introductionmentioning
confidence: 99%